Konsep Keluarga Sakinah pada Pasangan yang tidak Memiliki Keturunan di Desa Malimpung Kecamatan Patampanua Kabupaten Pinrang - Musdalifah; Aminah; Nurhikmah (Institut Agama Islam Negeri Parepare, 2023)
Forming a sakinah family is basically the awareness of the couple. This research aims to examine the concept of the sakinah family in married couples who do not have children in Malimpung Village, Patampanua District, Pinrang Regency, which is specifically reflected in two problem formulations, namely How do couples who do not have children understand the concept of the sakinah family in Patampanua District, Pinrang Regency and How does a childless couple in Malimpung Village try to form the Sakinah Family? This research uses field research with a descriptive qualitative approach. Data collection was carried out by means of observation, interviews and documentation of seven couples in Malimpung Village, which were analyzed by reducing data, presenting data as well as verifying and drawing conclusions. The theories used are functional structural theory and family communication theory. The results of this research show that every couple considers that children have very important value in the family, because children are also the hope of every couple in the family. Married couples who do not yet have children understand the concept of a sakinah family, namely a family that is able to maintain family harmony, be peaceful, comfortable, live in harmony with the family, communicate with each other, practice religious teachings, understand each other, and understand each other's strengths and weaknesses.